2006
DOI: 10.1590/s1413-70542006000600011
|View full text |Cite
|
Sign up to set email alerts
|

Amadurecimento de mamão formosa com revestimento comestível à base de fécula de mandioca

Abstract: RESUMOO mamão é fruta perecível, de vida útil pós-colheita curta. Novas tecnologias de conservação de produtos hortícolas com possibilidade de emprego em sistemas orgânicos têm sido desenvolvidas, a exemplo dos revestimentos comestíveis, que podem ser consumidos com o produto. Neste trabalho avaliou-se o amadurecimento de frutos de mamão Formosa Tainung 1 em temperatura ambiente, revestidos com película comestível à base de fécula de mandioca, que foi aplicada por meio de imersão dos frutos durante um minuto e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1
28

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 1 publication
(1 reference statement)
4
9
1
28
Order By: Relevance
“…However, there was no significant variation in both treatments due to storage for these parameters. These results differ from those obtained by Pereira et al (2006), who studied osmotically dehydrated fruit and reported a positive correlation between sugar contents and storage time.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, there was no significant variation in both treatments due to storage for these parameters. These results differ from those obtained by Pereira et al (2006), who studied osmotically dehydrated fruit and reported a positive correlation between sugar contents and storage time.…”
Section: Resultscontrasting
confidence: 99%
“…It was possible to verify that the Chroma of OD fruit ( Figure 5) has been positively affected by osmotic dehydration, reaching a maximum value around 23, between the 12 and the 15 th day of storage, proving, therefore, the red color tendency towards darkening, due to osmotic treatment. These results are similar to those reported by Pereira et al (2006), who evaluated the color of papaya dehydrated in sucrose solutions, and they are also similar to those obtained by Ito et al (2007), who studied the effect of osmotic dehydration upon mango color parameters. The process of osmotic dehydration utilized to preserve minimally processed guavas, associated to package and refrigeration, suggests effectiveness, since it slows the process of senescence and inhibits the respiratory metabolism of the product, thus providing maintenance of the physicochemical quality and increasing shelf life of the product.…”
Section: Resultssupporting
confidence: 91%
“…Cassava starch coating at 1, 2 and 3% on papayas, did not observe significant decreases in mass loss [21]. In accordance with this work, [22] reported that the use of hydrophilic coatings, such as starch, has limitations due to water vapor barrier properties.…”
Section: Resultssupporting
confidence: 82%
“…Os valores verificados foram inferiores aos observados por Fontes et al (2012), entre 0,15 e 0,37 g 100 g -1 MF, e de Morais et al (2007), entre 0,13 e 0,20 g 100 g -1 MF, mas estão de acordo com os valores apresentados por Oliveira-Jr. et al (2007), Lima et al (2009) e Gayosso-García et al (2010, cuja variação esteve entre 0,05 a 0,11 g 100 g -1 MF. Na literatura, também há relatos de não alteração na AT durante o amadurecimento do mamão Golden (CORRÊA et al, 2008), ou de aumento em mamões Tainung 01 (PEREIRA et al, 2006). Essa diversidade de resultados pode ser atribuída ao fato de essa variável ser dependente da época de colheita, dos níveis de adubação e do espaçamento, além de estar sujeita às variações de cada material genético na utilização de ácidos orgânicos como substratos do processo respiratório (SOUZA et al, 2009;FONTES et al, 2012).…”
Section: Oliveira; Vitória 2011)unclassified